2018
DOI: 10.1097/md.0000000000010720
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic acid use during total hip arthroplasty

Abstract: Administration of low-dose intravenous (IV) and intra-articular (IA) TXA does not appear to increase rates of adverse events and may be effective in minimizing blood loss, as reflected by Hb and Hct values following THA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 87 publications
0
17
0
Order By: Relevance
“…Husted et al [18] reported preoperative 10 mg/kg, followed by 1 mg/kg/h of continuous intravenous infusion of TXA for 10 h, and no increase in postoperative thrombosis-related events was observed. Another study reported [19] that intravenous infusion of aminocycline in total knee arthroplasty can reduce blood loss, but does not increase deep vein thrombosis and pulmonary embolism. Hines et al [20] reported that intravenous aminocycline can reduce the transfusion rate in total hip revision and does not increase the rate of deep vein thrombosis.…”
Section: Safety Of Intravenous Use Of Txamentioning
confidence: 99%
“…Husted et al [18] reported preoperative 10 mg/kg, followed by 1 mg/kg/h of continuous intravenous infusion of TXA for 10 h, and no increase in postoperative thrombosis-related events was observed. Another study reported [19] that intravenous infusion of aminocycline in total knee arthroplasty can reduce blood loss, but does not increase deep vein thrombosis and pulmonary embolism. Hines et al [20] reported that intravenous aminocycline can reduce the transfusion rate in total hip revision and does not increase the rate of deep vein thrombosis.…”
Section: Safety Of Intravenous Use Of Txamentioning
confidence: 99%
“…The studies were conducted in different areas, 3 in USA [14,15,19], 1 in Canada [13], 1 in Argentina [3], 1 in UK [16], and 1 in Germany [18]). Of the seven studies, 5 were retrospective COSs [3,[13][14][15]19], and 2 were prospective COSs [16,18]. Allogenic blood transfusion rate was reported in all seven studies [3, 13-16, 18, 19] and risk of VTE events in seven studies [3, 13-15, 16, 18, 19].…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%
“…Different dosages of TXA and surgical procedure were used in the studies (Table 1). VTE prophylaxis was clearly referred to in four studies [14,16,18,19]. Table 2 summarized the quality assessment of the selected studies, and the NOS score ranged from 7 to 9, which indicated acceptable quality for these studies.…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Husted et al [17] reported preoperative 10 mg/kg, followed by 1 mg/kg/h of continuous intravenous infusion of TXA for 10 h, and no increase in postoperative thrombosis-related events was observed. Another study reported [18] that intravenous infusion of aminocycline in total knee arthroplasty can reduce blood loss, but does not increase deep vein thrombosis and pulmonary embolism. Hines et al [19] reported that intravenous aminocycline can reduce the transfusion rate in total hip revision and does not increase the rate of deep vein thrombosis.…”
Section: Safety Of Intravenous Use Of Txamentioning
confidence: 99%